(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
This manuscript is a treatise on the study and analysis of entrepreneurs’ future. A literature review was conducted on major current management issues, and assumptions about future development and its impact were developed based on these findings. Management will evolve in the future to accommodate a new kind of global organization that is highly adaptable to a rapidly changing external environment. Running a virtual firm differs from running a traditional organization, and it will depend heavily on communication technologies in the future, necessitating the creation of a new corporation. According to the results, the organizational culture and attitudes of senior management based on individual perspectives and management styles are negatively linked to the benefits of perceived knowledge. A review of management efforts shows that not all of them have been successful. For future research, we recommend gathering data from employees, managers, or stockbrokers and comparing the results for more accurate information. Future study may potentially use a large number of case studies to compare their impact on various companies and industries.